Analisis Faktor Muat Trans Metro Pekanbaru Koridor Perum Pandau Permai - Pelita Pantai - Rizki Firmanda; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Trans Metro Pekanbaru (TMP) is a kind of ‘bus rapid transit’ in Pekanbaru. TMP has been operating since 2009 and there are many obstacles during the operation.  As time passes, the changes in the quantity of the passenger, quality of service and operation may possibly happen. Therefore, this research is conducted to determine the effectiveness of Trans Metro Pekanbaru (TMP), especially on Perum Pandau Permai – Pelita Pantai corridor with load factor as an indicator.  Bus TMP survey conducted by the method of observation and questionnaire. Observations adapted to the SK Dirjend Perhubungan Darat No. 687 at 2002. The results of the questionnaire were analyzed using Stated Preference Techniques. The survey observations were made in the TMP Buses that operate on the corridor I the number of surveyors is 11 people. While the questionnaire survey conducted by the two surveyors with the deployment of a random sample.  The obtained results of this research are the route characteristic of Trans Metro Pekanbaru corridor I is adequately effective based on the number of passengers, due to the load factor in this corridor is partially meet the load factor standard of SK Dirjen No. 687 at 2002 (70%) so it is fair optimal in serving the passenger movement. Based on the analysis, the value of load factor in corridor I have more than 70% in the afternoon, either on holiday or working days which obtained between Pelita Pantai towards Perum Pandau Permai route from BNI to Mekar Sari stations. From the results of statistical tests that have been carried out in this study, obtained the equation Y=7,932 – 0,045X1 – 0,031X2 + 0,000X3 + 0,015X4 for model selection with Trans Metro Pekanbaru attributes considered is the the waiting time (X1), speed (X2), rate (X3), and the comfort of the vehicle (X4).  Key words: Bus Rapid Transit, Trans Metro Pekanbaru, Load Factor